The Role of the Constitutional Court of the Russian Federation in Ensuring the Freedom of Labour Contract Parties - T. V. Russkikh (Сибирское юридическое обозрение, 2019)
In connection with the 25th anniversary of the Constitution of the Russian Federation, the study of the role of the Constitutional Court of the Russian Federation, including in the field of labour law, is particularly relevant. This article analyzes the activities of the Constitutional Court of the Russian Federation on constitutional control over the observance of freedom in the sphere of labor, the freedom of an employee and employer as parties to the labor contract. The legal positions elaborated by the court concerning the permissible restriction of rights and freedoms of a person and a citizen, which by virtue of their general nature can also be applied when assessing the admissibility of restriction by law of employee and employer freedom in the course of an employment contract, are studied. Some ordinances and definitions of the Constitutional Court of the Russian Federation, which, in the author’s opinion, explain in detail the current constitutional and legal meaning of the labor legislation norms in terms of the freedom of labor and freedom of economic activity. The focus of the article is on the latest acts of the Constitutional Court of the Russian Federation. It is concluded that the freedom of employee and employer as parties to an employment contract cannot be considered properly secured without constitutional control activities.